Application of dual-layer phosphor geometries for enhancing the optical properties of white-light LEDs - Phung Ton That; Hsiao-Yi Lee; Phan Xuan Le (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
This article compares the lumen output of two packages of two-remote phosphor (RP). The first package is flat dual-remote phosphor (FDRPS). The second package is concave dual-remote phosphor (CDRP). The dispersion qualities of the white-light-emitting diode are different as a result of their different cover designs, leading to a disparity between the FDRPS and CDRPS configurations. The results of the study show that the FDRPS package yields a lumen output superior to that of the CDRPS package. In the article, we can also see how the space among the phosphor films (?1) and the space among the phosphor film and the light emitting diodes (LED) outer side (?2) might affect the light characteristics in the CDRPS model. As the indicated distances shift, the characteristics of dispersion and absorptivity in the distant phosphor film will shift as well. Such an occurrence can have an impact on chromatic uniformity as well as optical performance in white light emitting diodes (WLEDs). If we modify the  and  values, it is necessary to change the phosphor YAG:Ce3+ concentration in the WLEDs to keep the correlated color temperature at 8500 K.